Pelaksanaan Gerakan Lima Literasi (Literasi Membaca, Numerasi, Sais, Finansial, Dan Budaya-Kewarhanegaraan) Di SDN 009 Bina Baru, SDN 003 Bina Baru Kec. Kampar Kiri Tengah, Dan SDN 18 Pekanbaru - Oriza Sativa Putri; Yulia Afriani; Ibnu Aufin Azhari (Universitas Maritim AMNI Semarang, 2023)
The background in this study is the lack of literacy skills in reading and writing, financial, sanis, numeracy and citizenship among students in three schools in the Kampar and Pekanbaru areas. The low ability of the five literacy is thought to affect student achievement. This is due to the low value of student achievement at school. In this study the authors used five literacy, namely reading literacy, numeracy, science, finance, and cultural-citizenship which were applied in three different schools in the Kampar district and Pekanbaru city, namely SDN 009 BINA BARU, SDN 003 Bina Baru Kec. Kampar Kiri Tengah, and SDN 18 Pekanbaru. The research objective is to find out about; 1) Knowing literacy skills in reading, numeracy, science, finance, and cultural-citizenship 2) Knowing the level of learning achievement through these five literacy and 3) Knowing the effect of these five literacy skills on student achievement at SDN 009 BINA BARU, SDN 003 Bina Baru Kec. Kampar Kiri Tengah, and SDN 18 Pekanbaru. In this study using a qualitative approach. the purpose of using this approach is to explain the implementation of the five literacy movement which was carried out to students in three elementary schools in Pekanbaru and Kampar. This research was conducted in three schools, SDN 009 BINA BARU, SDN 003 Bina Baru Kec. Kampar Kiri Tengah, and SDN 18 Pekanbaru. the results of the implementation of the five literacy movement in students and interviews that have been conducted by researchers, implementation at the habituation stage of the School Literacy Movement at SDN 009 BINA BARU, SDN 003 Bina Baru Kec. Kampar Kiri Tengah, and SDN 18 Pekanbaru are in the good category, students can receive new literacy that has never been done in their previous school